1989
DOI: 10.1111/j.1600-0404.1989.tb03839.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide effects on cerebral blood flow in acute reversible ischemia

Abstract: Cerebral blood flow (CBF) was studied in 4 patients with acute reversible ischemia (RIND). To test the ischemic areas' vasoreactivity, CBF was measured by the Xenon-133 inhalation method, before and after acetazolamide injected intravenously. At the baseline CBF study, 3 patients presented hypoperfused areas while one patient had increased CBF over the affected hemisphere. The acetazolamide test, showed in this latter case a "steal phenomenon" while in the other 3 an increase of perfusion was evidenced, in are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…one clinical study has reported that vasomotor responses to acidosis remain intact in the vicinity of ischemic foci (Di Piero et al, 1989).…”
Section: Fig 2 Possible Protective Effects Of Acidosis Duringmentioning
confidence: 99%
“…one clinical study has reported that vasomotor responses to acidosis remain intact in the vicinity of ischemic foci (Di Piero et al, 1989).…”
Section: Fig 2 Possible Protective Effects Of Acidosis Duringmentioning
confidence: 99%